Graphene layers on semi-finite 1D asymmetric periodic structure of Si/Glass materials with defect of nematic liquid crystal for a sensor device. (29th March 2019) - Singh, Pawan; Thapa, Khem B; Kumar, Narinder; Pal, Krishan; Kumar, Devesh
Abstract: In this work, the effective absorption property of graphene layers on one-dimensional periodic structure (1DPS) of Si/Glass materials with nematic liquid crystal (NLC) as a defect has been studied theoretically. The graphene sheets are stuck on the one end of Si as well as Glass of the semifinite periodic structure of Si/Glass materials. Now the nematic liquid crystal (NLC) is embedded with the semifinite periodic structure of Si/Glass materials containing graphene layers. Using the transfer matrix method (TMM), the transmission and absorption behavior of graphene layers on semi-finite 1D asymmetric periodic structure of Si/Glass materials with a defect of nematic liquid crystal have been studied. Our results suggest that defect layer of nematic liquid crystal (NLC) in the semi-finite 1D asymmetric periodic structure with graphene layers (G), (Si∣Glass) m ∣G∣NLC∣G∣(Si∣Glass) n with m = 3 & n = 5, may be used as sensor device due to high absorption behavior for a specific director angle of molecules of the nematic liquid crystal (NLC). Besides this, the absorption behavior of the structure for TE mode, (Si∣Glass) 3 ∣G∣NLC∣G∣(Si∣Glass) 5, is more effective in comparison to the absorption behavior of the structure for TM mode at normal incidence wave.